2023
DOI: 10.3390/children10101664
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Characteristics and Weight Status of Early Adolescents (Aged 12–14) in Montenegro; Urban–Rural and Regional Differences

Borko Katanic,
Dusko Bjelica,
Mima Stankovic
et al.

Abstract: The aim of this study was to determine urban–rural and regional differences in anthropometric characteristics among adolescents aged 12–14, as well as to present the prevalence of weight status. A total of 534 adolescents aged 12–14 from primary schools across Montenegro participated in this cross-sectional study (283 boys, aged 13.52 ± 0.42, body height 169.43 ± 8.89, body weight 60.54 ± 13.47; 251 girls, aged 13.51 ± 0.40, body height 165.54 ± 6.67, body weight 55.28 ± 9.27). The sample was divided by geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…A Chinese study revealed that urban adults tended to exhibit higher BMI than their rural counterparts, with the overall urban-rural BMI disparity diminishing since 2004, particularly among women [ 17 ]. Similarly, a study in Montenegro found that girls and boys in urban areas displayed lower BMI values than their rural counterparts, showcasing significant differences in BMI between urban and rural adolescents [ 18 ]. These findings underscore the BMI variations in urban and rural populations across diverse regions.…”
Section: Reviewmentioning
confidence: 99%
“…A Chinese study revealed that urban adults tended to exhibit higher BMI than their rural counterparts, with the overall urban-rural BMI disparity diminishing since 2004, particularly among women [ 17 ]. Similarly, a study in Montenegro found that girls and boys in urban areas displayed lower BMI values than their rural counterparts, showcasing significant differences in BMI between urban and rural adolescents [ 18 ]. These findings underscore the BMI variations in urban and rural populations across diverse regions.…”
Section: Reviewmentioning
confidence: 99%